Perceptions of insecurity and social cohesion in building resilience among residents in north-east Nigeria - Butu, Hauwa Mai; Hassan, Mohammad Mujaheed; Hashim, Ahmad Hariza; Ahmad, Nobaya (Human Resource Management Academic Research Society, 2023)
Building resilience is vital to devising the ability to overcome challenges, especially in times of insecurity. The objective of this study is to assess the level of perception of insecurity and social cohesion of residents in northeast Nigeria. The study also determines the influence of the perception of insecurity, social cohesion, length of stay, and age on resilience. The study sampled 383 respondents in Gwange, Bolori, Yerwa and Mai-Sandari of Maiduguri metropolis. The data was analysed using descriptive and inferential statistics. The findings revealed a moderate level of both perceptions of insecurity and social cohesion. The study also indicates that while the perception of insecurity predicts resilience (? = .297, p < .000) and social cohesion (? = .444, p < 0.00), age and length of stay (? = -.012, p < .770 and (? = -.041, p < .324) do not influence residents' resilience in Maiduguri. This study recommended that community engagement programs that aim to foster a sense of unity, and collaboration among residents, strengthen the existing social support networks within the neighbourhood. Similarly, community involvement in the decision-making process should be implemented and any form of initiative should be culturally sensitive and aligned with the needs of the people.